RESPON TANAMAN OKRA MERAH (Abelmoschus esculantus L.) TERHADAP PEMBERIAN CUKA KAYU - Faridatul Mukminah Mukminah; Ruarita Ramadhalina Kawaty; Meri Fitriyani (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
ABSTRACT This study aims to determine the best concentration of wood vinegar on the growth and yield of okra plants (Abelmoschus esculantus L). This research has been carried out in Kenten Laut, Sukamaju, Sako, Palembang Indonesia from October 2017 to January 2018. The design of the research was Randomized Block Design (RBD) with 5 (five) treatments and 5 (five) replications. The treatment studied was the concentration of wood vinegar, namely P0 = control, P1 = 10 ml of wood vinegar/liter of water, P2 = 20 ml of wood vinegar/liter of water, P3 = 30 ml of wood vinegar/liter of water, P4 = 40 ml of wood vinegar/ liter of water. The variables observed were plant height, number of leaves, number of branche, age of flowering, number of flowers per plant, number of fruit per plant, fruit production (yield) per plot. Based on the results of the study can be concluded that wood vinegar with concentration of 40 ml/liter water (P4) increased plant height, number of leaves, amount of fruit, fruit weight per plant, and the yield per plot.Keywords: ocra, wood vinegar